Integrated cybersecurity framework for enhanced threat detection and incident response in the digital era / Azlin Ramli ... [et al.] - Ramli, Azlin; Darus, Mohamad Yusof; Mohd Yussoff, Yusnani; Azni, Badri; Kanqi Xie (Universiti Teknologi MARA, 2025)
This research presents a novel cybersecurity framework aimed at improving threat detection and incident response in today's complex digital environment. The framework integrates three key components: advanced threat detection, accelerated incident response, and continuous risk assessment, adopting a holistic and adaptive approach. It leverages machine learning (ML) and artificial intelligence (AI) to proactively identify and counter evolving cyber threats, moving beyond traditional reactive systems. The advanced threat detection element utilizes AI-driven analytics to spot anomalous patterns and forecast potential vulnerabilities, thus enhancing threat visibility. The accelerated incident response streamlines automated responses to common threats, significantly cutting response times. Complementing these is a comprehensive risk assessment, which provides quantifiable resilience metrics for ongoing monitoring and improvement. The framework's effectiveness is validated through extensive testing and real-world case studies across various sectors, including finance, education, healthcare, and manufacturing. Results indicate substantial improvements in key performance indicators, such as reduced false positives and minimized downtime during security incidents. Despite its advancements, the research identifies implementation challenges, including resource intensity, the need for adaptable components across different organizations, and the importance of human factors like employee training. Future research will address these issues, focus on enhancing the framework's adaptability, and explore the integration of emerging technologies, such as blockchain, to bolster its effectiveness in combating sophisticated cyber threats. Ultimately, this initiative seeks to promote innovation and growth in the global digital economy by proactively managing cybersecurity risks.